The Influence of Age and Nutritional Status on Heat Strains Incident on Workers of Brem Making in Kaliabu Village, Madiun - Siska Wahyu Handayani; Sri Hernawati; Farida Wahyu Ningtyias (Humanistic Network for Science and Technology (HNST), 2021)
Workers at brem industries are particularly at risk of heat strains at work. This is due to the age factor of the workers as well as the nutritional status that can be the main cause in case of heat strain events. Purpose of this study was to find out the level of influence of age factor and nutritional status on heat strain events in brem industries workers in Kaliabu village, Madiun. Quantitative observational analytical research with a cross sectional approach where the sample of research amounted to 157 respondents from a total population of 266 workers. Regression test with Amos 23 tools in analyzing data. Result in the age variable was 0.072 and for the nutritional status obtained the result of 0.079 against the incidence of heat strains where both variables had a significant influence on heat strains. So that the need for spatial planning and fulfillment of good nutrition by industry managers. Keywords: heat strain; nutritional status; age; brem; industries